BOOK REVIEW of Conceptualizing the Process of Radicalization among Ethnic and Religious Groups - Georgi Stankov (Bulgarian Journal of International Economics and Politics)
Petar Atanassov. Conceptualizing the Process of Radicalization among Ethnic and Religious Groups. Plovdiv: Publishing Complex VUSI. 2024. 227 pages. ISBN (print): 978-610-7774-02-3 The reviewed book seeks to summarise and analyse the factors that influence the emergence and development of the radicalization processes on ethnic and religious bases, as well as their subsequent impact on national and international security. Through critical involvement with the existing theories and paradigms, the author develops a specific perspective on radicalization processes in the modern world. With a background of a professional historian and building on direct observations of public life in several countries, Petar Atanassov boldly delves into present-day and historical appearances of complicated social and political phenomena pertinent to radicalization. The study outlines the factors related to ethno-religious radicalization such as migration processes, social discrimination, religious propaganda, collective utopias, terrorism, etc. The author scrutinises a number of factors of radicalization, such as propaganda messages, instrumentalization of social problems for the purposes of radicalizing elements, and introduces a review of empirical data on the social profile of radicals in contemporary societies and on existing programs for de-escalation and de-radicalization of at-risk communities, for rehabilitation and reintegration of persons who articipated in extremist groups, etc.